Grazing affects vegetation diversity and heterogeneity in California vernal pools. Issue 4 (15th March 2021) - Michaels, Julia; Batzer, Evan; Harrison, Susan; Eviner, Valerie T.
Abstract: Disturbance often increases local‐scale (α) diversity by suppressing dominant competitors. However, widespread disturbances may also reduce biotic heterogeneity (β diversity) by making the identities and abundances of species more similar among patches. Landscape‐scale (γ) diversity may also decline if disturbance‐sensitive species are lost. California's vernal pool plant communities are species rich, in part because of two scales of β diversity: (1) within pools, as species composition changes with depth (referred to here as vertical β diversity ), and (2) between pools, in response to dispersal limitation and variation in pool attributes (referred to here as horizontal β diversity ). We asked how grazing by livestock, a common management practice, affects vernal pool plant diversity at multiple hierarchical spatial scales. In terms of abundance‐weighted diversity, grazing increased α both within local pool habitat zones and at the whole‐pool scale, as well as γ at the pasture scale without influencing horizontal or vertical β diversity. In terms of species richness, increases in α diversity within habitat zones and within whole pools led to small decreases in horizontal β diversity as species occupancy increased. This had a dampened effect on species richness at the γ (pasture) scale without any loss of disturbance‐sensitive species. We conclude that grazing increases species richness and evenness (α) by reducing competitive dominance, without large disruptions to the critical spatial heterogeneity (β) that generates high landscape‐level diversity (γ).